Literature Review : Implementasi Kurikulum Merdeka dalam Pembelajaran IPA di Sekolah Dasar (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
The Merdeka Curriculum is a new educational framework in Indonesia that emphasizes student-centered learning, flexibility, and contextual understanding. This literature review aims to explore the implementation of the Merdeka Curriculum in the teaching of Natural and Social Sciences (IPAS) at the elementary school level. Several studies show that project-based learning approaches can enhance students' critical thinking and collaboration skills. However, challenges such as limited teaching resources, lack of teacher readiness, and misunderstanding of the curriculum structure are still prevalent. This review also identifies several efforts made to address these issues, including continuous professional development for teachers, collaborative learning communities, and school leadership support. The findings suggest that successful implementation of the Merdeka Curriculum in IPAS requires a comprehensive and collaborative effort from educators and stakeholders.